2009
DOI: 10.1002/bit.22285
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic analysis of biodegradation pathways

Abstract: Microorganisms provide a wealth of biodegradative potential in the reduction and elimination of xenobiotic compounds in the environment. One useful metric to evaluate potential biodegradation pathways is thermodynamic feasibility. However, experimental data for the thermodynamic properties of xenobiotics is scarce. The present work uses a group contribution method to study the thermodynamic properties of the University of Minnesota Biocatalysis/Biodegradation Database. The Gibbs free energies of formation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 48 publications
0
44
0
Order By: Relevance
“…We used a group contribution method (Jankowski et al, 2008) to estimate the Gibbs free energy of the individual reactions and calculated the cumulative energy of the pathway. This method provides a means of estimating the thermodynamic properties of biochemical reactions and has been shown to be a viable tool to provide a priori estimates of the thermodynamic feasibility of biodegradation pathways (Finley et al, 2009). We have previously shown how to treat biodegradation reactions involving oxygenase and reductive dechlorination reactions (Finley et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a group contribution method (Jankowski et al, 2008) to estimate the Gibbs free energy of the individual reactions and calculated the cumulative energy of the pathway. This method provides a means of estimating the thermodynamic properties of biochemical reactions and has been shown to be a viable tool to provide a priori estimates of the thermodynamic feasibility of biodegradation pathways (Finley et al, 2009). We have previously shown how to treat biodegradation reactions involving oxygenase and reductive dechlorination reactions (Finley et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…This method provides a means of estimating the thermodynamic properties of biochemical reactions and has been shown to be a viable tool to provide a priori estimates of the thermodynamic feasibility of biodegradation pathways (Finley et al, 2009). We have previously shown how to treat biodegradation reactions involving oxygenase and reductive dechlorination reactions (Finley et al, 2009). Since much of the free energy released in oxygenase reactions is associated with the reduction of oxygen to water and is not coupled to the generation of electron carriers, we only report the free energy change that is available for cell mass maintenance and growth.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the difference in dechlorination pathways between experimentally observed and theoretically calculated proves the necessity of a multivariable analysis for field applications. Recently, Finley et al (2009) reported that thermodynamic analysis alone could not predict the biodegradation pathway of xenobiotics. Rather, thermodynamic analysis combined with reaction pathway prediction tools (Ellis et al, 2008) can assist the prediction of degradation pathways of these compounds.…”
Section: Dechlorination Product Isomer Distribution Based On Free Enementioning
confidence: 99%
“…When applied to a starting substrate and its progeny, all possible enzymatic reactions given these generalized enzyme operators are unfurled, including a large number of novel reactions. For a number of different systems, it has been shown that the computational framework identifies hundreds to thousands of novel biochemical pathways from a starting compound to a target compound [16,20,21]. Various screening methods were applied to cull this large set of novel pathways to a manageable number of attractive candidates, including pathway length, number of novel intermediates, thermodynamic landscape, and pathway flux analysis [22] based on metabolic flux analysis and thermodynamic metabolic flux analysis [15,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…One approach that has emerged recently utilizes a computational framework based on graph theory that creates complex networks of reactions and compounds based on generalized enzyme reactions [13][14][15][16][17][18][19][20]. Substrates and products of reactions are represented by matrices, and reactions are carried out through addition of reaction operators.…”
Section: Introductionmentioning
confidence: 99%